MoU signing ceremony & actuary summer camp in University of Essex, UK / Siti Salihah Shaffie - Shaffie, Siti Salihah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The signing of this MoU confirms great opportunity for UiTM graduates who wish to pursue a degree at University of Essex. Students will also be granted with £2000 for their study at the university. Conjoined with the MoU handover ceremony was the Actuary Summer Camp programme. A total of 10 stu-dents from FSKM had participated and facilitated by three lecturers from the same faculty. The programme also invited three alumni of FSKM to share their experiences of studying at the university.